Collateral sensitivity between aminoglycosides and beta-lactam antibiotics depends on active proton pumps. (November 2017) - Azimi, Leila; Rastegar Lari, Abdolaziz
Abstract: Background: Selection inversion is the hypothesis for antibiotic resistant inhabitation in bacteria and collateral sensitivity is one of the proposed phenomena for achievement of this hypothesis. The presence of collateral sensitivity associated with the proton motivation pump between the aminoglycosides and beta-lactam group of antibiotics is one of the examples of collateral sensitivity in some studies. The aim of this study was to demonstrate that collateral sensitivity between aminoglycosides and beta-lactam antibiotics associated with proton motivation pump may not be true in all cases. Methods: In this study, 100 Pseudomonas aeruginosa were surveyed. Gentamicin and imipenem-resistant strains were confirmed by disc diffusion method and MIC. Active proton motivation pumps were screened by pumps inhibitor. Semi-quantitative Real-Time PCR assay was used to confirm gene overexpression. Results: Seventy-six and 79 out of 100 strains were resistant to gentamicin and imipenem, respectively. Seventy-five strains were resistant to both gentamicin and imipenem. The results of proton pump inhibitor test showed the involvement of active proton motivation pump in 22 of 75 imipenem- and gentamicin-resistant strains. According to Real – Time PCR assay, mexX efflux gene was overexpressed in the majority of isolates tested. Discussion: The collateral sensitivity effect cannot explain the involvement of active proton motivation pumps in both imipenem and gentamicin-resistant strains simultaneously. Active and/or inactive proton pump in gentamicin-sensitive and/or resistant strains cannot be a suitable example for explanation of collateral sensitivity between aminoglycosides and beta-lactam antibiotics. Highlights: This study indicated that involvement of proton motivation to gentamicin resistance. This study indicated that involvement of proton motivation to imipenem resistance. Pumps that need for transport aminoglycoside can be different with that necessary for resistance to beta-lactam. The results of this study indicated that collateral sensitivity between gentamicin and imipenem cannot be true at all.